Application of Electronic Certificates as a Form of Legal Protection & Land Tenure Hak - Damianus Krismantoro (Budapest International Research and Critics University, 2022)
The rapid advancement of information and communication technology should be accompanied by the most recent legal discoveries in order to balance society's increasingly complex dynamics, because if there is no law, the law would constantly lag behind the times. The government is attempting to make a new legal breakthrough with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1 of 2021 concerning Electronic Certificates, which aims to realize the modernization of land registration to improve indicators of ease of doing business and public services to the community, while also optimizing the use of information technology and communication by implementing electronic-based land services. The research method employed in this study is normative legal research (doctrinal legal research). In this study, the approach method is statutory, that is, it is based on legislation and regulations. The study's findings reveal that the conversion of land certificates, which were formerly in the form of documents (letters), to electronic format, which has raised concerns in the community, is unwarranted because both have binding legal force under Indonesian procedural law. The Law of the Republic of Indonesia Number 19 of 2016 about Electronic Information and Transactions and the Regulation of the Minister of ATR/BPN Number 1 of 2021 concerning Electronic Certificates provide legal protection for the use of electronic certificates.